SIMULASI DAN IMPLEMENTASI FIREWALL BERBASIS SQUID UNTUK KEAMANAN INTERNET - Iwan Agi Berutu; Khildan Rifail Azis; Yunita Rahmi; Dedy Kiswanto (Jurnal Teknologi Informasi dan Komputer, 2025)
Network security is a crucial aspect of information systems, especially in the internal networks of institutions or organizations. This study aims to develop a Squid-based firewall system as an effective network security solution to control and filter internet access. The method used involves open-source system development by utilizing Debian Linux and Squid Proxy software. Installation and configuration processes were conducted to manage access restrictions based on HTTP/HTTPS protocols, IP addresses, and usage time. The implementation results show that the developed firewall system is capable of blocking unwanted websites, regulating access times, and recording user activities through system logs. This system also offers ease for administrators in monitoring and managing network traffic efficiently. With this approach, institutions or organizations are expected to enhance their internal network security without incurring high licensing costs. This research contributes to the utilization of open-source technology for independently and affordably addressing network security needs.